EMMA - Austen, Jane, 1775-1817, author 199816 (London, England : Penguin Books Ltd, 1994)
Emma is the culmination of Jane Austen's genius, a sparkling comedy of love and marriage. Emma Woodhouse is introduced to us a 'handsome, clever and rich' and, according to Jane Austen, a heroine 'which no one but myself would like'. Yet such is Emma's spirited wit that, despite her superior airs and egotism, few readers have failed to succumb to her charm. The comedy turns on Emma's self-appointed role as energetic match-maker for her sweeet, silly friend Harriet. Emma herself, meanwhile, is confidently immune to the ckarms of the male sex. Her emotional coming of age is woven into what Ronald Blythe has called 'the happinest of love stories, the most friendishly difficult of detective stories and a matchless repository English wit'.